PENGARUH PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KEANEKARAGAMAN HAYATI KELAS X SMA NW SURALAGA - Zohratul Anwariah; R. Didi Kuswara (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2019)
This study aims to determine the effect of Problem Solving on critical thinking skills and student learning outcomes on the subject of biodiversity class X SMA Suralaga. This research is a quase experiment with a non equivalent pretest posttest control group design. The population in this study were all students of class X and the sample of this study was class XC and XD using simple random sampling techniques. Class XC totaling 22 students as a control class with direct instruction techniques and class XD totaling 22 students as an experimental class who were treated with Problem Solving. The research instrument used was a test of learning outcomes in the form of pre-test and post-test, critical thinking questions and observation sheet of the implementation of learning. The results showed that the average value of experimental class learning outcomes 72.99, while the average value of the control class was 60.73. The average value of critical thinking experimental class 78.05, while the average value of the control class 59.86. Based on the results of hypothesis testing with regression tests obtained significance of learning outcomes 0,000 less than the significance of 0.05 (0,000 <0.05) as well as the significance value of critical thinking 0.00 smaller than the significance value of 0.05 (0.00 <0, 05). The conclusion from the results of this study that there is an influence of problem solving on critical thinking skills and student learning outcomes..